A Guide to Citrus Disease Identification - Stephen H. Futch (EDIS, 2020)
Citrus trees in both commercial and dooryard plantings can exhibit a host of symptoms reflecting various disorders that can impact their health, vigor, and productivity to varying degrees. Identifying symptoms correctly is an important aspect of management, as inappropriate remedial applications or actions can be costly and sometimes detrimental.